The predictive role of lymphocyte subsets and laboratory measurements in COVID-19 disease: a retrospective study - Lin Wang; Jun Chen; Jun Zhao; Feng Li; Shuihua Lu; Ping Liu; Xu-hui Liu; Qin Huang; He Wang; Qing nian Xu; Xiaomin Liu; Shijun Yu; et al. (Therapeutic Advances in Respiratory Disease, 2021)
Aim: The aim of this study was to investigate the predictive role of lymphocyte subsets and other laboratory measurements in patients with COVID-19. Methods: Electronic medical records of adult patients with confirmed diagnosis of COVID-19 from the Shanghai Public Health Clinical Center were reviewed retrospectively to obtain relevant data. Results: The mean age of patients was 40.98 ± 15.95 years, with 58% of the patients being males. The cutoff values at the intensive care unit (ICU) admission, mechanical ventilation, and mortality were CD4+ cells (267, 198, and 405), CD8+ cells (263, 203, and 182), and CD4+ /CD8+ cells (1.4, 1.8, and 1.4). The cutoffs below these values indicate the higher chances of disease progression. Higher CD4+ cell count led to lesser chances for ICU admission [odds ratio (OR) (95% confidence interval (CI): 0.994 (0.991, 0.997); p  = 0.0002] and mortality [OR (95% CI): 0.988 (0.979, 0.99); p  = 0.001], higher CD8+ count was an independent risk factor for ICU admission. T-cell count positively correlated with total lymphocyte count and platelets, while negatively correlated with D-dimer and lactate dehydrogenase (LDH). Among patients with non-severe COVID-19, median CD8+ T cell, CD4+ T cell, total lymphocyte count, and platelets were 570, 362, 1.45, and 211, respectively, while median values decreased to 149, 106, 0.64, and 172, respectively, in patients with severe COVID-19. Conclusion: Lower T lymphocyte subsets were significantly associated with higher admission to ICU, mechanical ventilation, and mortality among patients with COVID-19. A cutoff value of ICU admission, mechanical ventilation, and mortality below CD4+ cells (267, 198, and 405), CD8+ cells (263, 203, 182), and CD4+/CD8+ cells (1.4, 1.8, 1.4) may help identify patients at high risk of disease progression. The continuous evaluation of laboratory indices may help with dismal prognosis and prompt intervention to improve outcomes.